Comparative evaluation of different micro irrigation methods in crop geometry of banana - ASSIYA LEBEEHA K. A; Bhavya P. R; Sreekanth K. S; Er. T. D Raju (Guide) (Tavanur 2008 Kelappaji College of Agricultural Engineering and Technology)
Comparative evaluation of different micro irrigation methods in crop geometry of banana
Comparative evaluation of different micro irrigation methods in crop geometry of banana